Tuberculous osteomyelitis of the mandible - Nirima Oza; Karoon Agrawal (Wolters Kluwer Medknow Publications, 2013)
In developing countries, tuberculosis is still a prevalent health problem. Purpose of this short communication is to draw an attention that pus discharging extra oral sinus in relation to lytic lesion of the mandible without any odontogenic or any other cause could be due to tubercular infection.